Energy efficiency policies across the EU and their impact on alleviating energy poverty: Insights from the MURE database - Anna Lena Heller; Iska Brunzema; Barbara Schlomann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
Energy poverty, characterized by a lack of access to reliable and affordable energy services, persists to be a critical global challenge with far-reaching socio-economic implications. As this also remains to be an urgent issue in the EU, measures alleviating energy poverty are critical to ensure a just energy transition. Instead of being a co-benefit of packages such as the Energy Efficiency first principle and only tackling the issue via social policies, the recast of the Energy Efficiency Directive (EED) and the Energy Performance of Buildings Directive (EPBD) mandate are treating energy poverty via energy efficiency measures. Thus, this paper focuses on energy efficiency policies that address energy poverty, based on the MURE database which contains energy efficiency measures of the EU Member States, Switzerland, and Energy Union partners. Recognizing the diverse nature of energy poverty across the EU, the European Commission guides Member States to adopt individualized approaches to combat this issue. To illustrate the different contexts and strategies, the paper includes case studies from Greece, Finland, Ireland, Latvia, and India. In the upcoming years, further policy measures alleviating energy poverty are to be expected due to the new requirements for the Member States in the EED and EPBD recast. This paper is intended to show examples of measures alleviating energy poverty that could be used to implement the future EU requirements in the Member States.
Keywords: 330; Energy poverty; energy efficiency policy; EU policy; case studies; reporting requirements